Bisimulations for Temporal Logic - Kurtonina, Natasha; De Rijke, Maarten (Journal of Logic, Language and Information, 1997)
We define bisimulations for temporal logic with Since and Until. This new notion is compared to existing notions of bisimulations, and then used to develop the basic model theory of temporal logic with Since and Until. Our results concern both invariance and definability. We conclude with a brief discussion of the wider applicability of our ideas.
Keywords: definability; expressive power; modal and temporal logic; model theory